Real-time Simulations on High-Performance Z-Source PV-Grid-Tied Inverters with DC Charger for EV Applications (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
Solar power is the most prevalent green energy source for household and semi-commercialapplications. Using energy storage devices, fluctuations in solar energy collecting can be reduced(ESS). Solar electricity can also be utilized to charge electric vehicle batteries, reducing reliance onthe grid. To qualify as such converters, they must have a limited number of steps and a separation. Itis possible to eliminate multiple stages of conversion by using the Z-source inverter (ZSI) topology.The use of passive materials allows for the incorporation of ESS. To charge the batteries of electricvehicles using direct current, this article describes the design, building, and operation of a modifiedZSI equipped with a split primary separated battery charger. Simulated results have been used todemonstrate the feasibility of the proposed converter's operation.